2008
DOI: 10.5964/ijpr.v2i2.23
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Satisfaction among South Asian Canadians: The Role of ‘Complementary-Equality’ and Listening to Understand

Abstract: This study explored the ways in which adherence to traditional marital expectations in ones marriage was related to styles of interpersonal listening and marital satisfaction among IndoPakistanis living in a Western country. Participants (n = 114) were recruited from a large metropolitan city in Canada, were married, and their ages ranged from 19 to 67 years. They completed measures of marital satisfaction, listening styles, and traditional orientation to marriage. Results indicated that greater adherence to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…This subscale includes items such as satisfaction with each other's educational and occupational achievements, sharing of cultural, religious and familial ideals, and involvement of extended family in their marriage. The RRAS‐C had previously demonstrated high internal consistency (α = .93) and significant positive correlations with measures of active listening among a sample of 114 South Asian marital partners (Ahmad & Reid, ). In the present study, Cronbach's alpha for the 23‐item RRAS‐C was .87 and .92 in the first and final sessions, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This subscale includes items such as satisfaction with each other's educational and occupational achievements, sharing of cultural, religious and familial ideals, and involvement of extended family in their marriage. The RRAS‐C had previously demonstrated high internal consistency (α = .93) and significant positive correlations with measures of active listening among a sample of 114 South Asian marital partners (Ahmad & Reid, ). In the present study, Cronbach's alpha for the 23‐item RRAS‐C was .87 and .92 in the first and final sessions, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Results of Valiant and Valiant (1993) and Twenage et al (2003) indicated that marital adjustment in couples declined in the first 10 years of marriage, with the lowest level of satisfaction for the couples with teenagers. This trend was then followed by the first child to the last child leaving home (Fincham & Beach, 2010;Umberson et al, 2005), by "empty nest" situation (McGoldrick et al, 2010), and, lastly, by retired couples (Aslinia, 2010;Ahmad & Reid, 2008).…”
Section: Overview Of Literature From the Western Contextmentioning
confidence: 97%
“…However, partners who report suffering from a work-life imbalance experience work stress and their relationship becomes less satisfying overtime, which leads to relationship dissolution (Debrot, Siegler, Klumb, & Schoebi, 2018;Yucel, 2012). When relational partners perceive that their partner is listening to them to understand their situation, they are more likely to experience "we-ness" and relationship satisfaction, which may reduce the likelihood of relationship dissolution (Reid, Dalton, Laderoute, Doell, & Nguyen, 2006;Ahmad & Reid, 2008).…”
Section: Listening Satisfaction As a Mediator Of Work-life Balance Anmentioning
confidence: 99%